Equations of Motion Near Cyclotron Resonance - Albert, Jay M.; Artemyev, Anton; Li, Wen; Gan, Longzhi; Ma, Qianli (Frontiers in Astronomy and Space Sciences, 2022)
This work compares several versions of the equations of motion for a test particle encountering cyclotron resonance with a single, field-aligned whistler mode wave. The gyro-averaged Lorentz equation produces both widespread phase trapping (PT) and ``positive phase bunching'' of low pitch angle electrons by large amplitude waves. Approximations allow a Hamiltonian description to be reduced to a single pair of conjugate variables, which can account for PT as well as phase bunching at moderate pitch angle, and has recently been used to investigate this unexpected bahavior at low pitch angle. Here, numerical simulations using the Lorentz equation and several versions of Hamiltonian-based equations of motion are compared. Similar behavior at low pitch angle is found in each case.